Simultaneous 3D observation of different kinetic subprocesses for precipitation in a T-mixer - Gradl, Johannes; Peukert, Wolfgang (Chemical Engineering Science, 2009)
A coupled direct numerical simulation (DNS)—population balance equation (PBE)–DLVO approach is presented to calculate the product properties of particles originating from precipitation in a T-mixer. A special focus is given to the coupling of different subprocesses such as mixing, nucleation, growth, stabilization and aggregation for a rapid precipitation process. Based on the predictive computation of the resulting particle size distributions (PSD) full 3D-field information of all transient parameters are accessible, e.g., supersaturations, nucleation rates, particle sizes and stabilities. By interpolating the kinetic data, relevant subprocesses can be visualized and studied separately in the mixer. The resulting PSDs are predicted for different conditions where aggregation can be neglected. For unstable conditions aggregation and transient stabilization effects are determined by the DLVO theory. The size of the particles, their surface potential and the ionic strength of the solution vary extensively during the solid formation process. The dynamic evolution of the particle stability leads to a better description of the PSD based on the DNS–PBE–DLVO approach for unstable conditions and allows to develop strategies how to better stabilize particles. This approach is verified for barium sulphate precipitation but can be transferred to any other ionic system for which the relevant material specific data are known.